Physical properties of the magnetically frustrated very-heavy-fermion compound YbCu4Ni - Sereni, Julian Gustavo Renzo (2018)
The physical properties of the very-heavy-fermion compound YbCu4Ni were characterized through structural, magnetic, thermal, and transport studies along nearly four decades of temperature ranging between 50 mK and 300 K. At high temperature, the crystal electric field level splitting was determined with Δ1(Γ6)=85K and Δ2(Γ8)≈200K, the latter being a quartet in this cubic symmetry. An effective magnetic moment μeff≈3μB is evaluated for the Γ7 ground state, while at high temperature the value for a Yb3+ ion is observed. At low temperature this compound shows the typical behavior of a magnetically frustrated system undergoing a change of regime at a characteristic temperature T∗≈200mK into of Fermi-liquid-type "plateau" of the specific heat: Cm/T|T→0 = const. The change in the temperature dependence of the specific heat coincides with a maximum and a discontinuity in respective inductive and dissipative components of the ac susceptibility. More details about the nature of this ground state are revealed by the specific heat behavior under applied magnetic field.